1996
DOI: 10.1111/j.1095-8649.1996.tb01489.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity and feeding in larval Premnas biaculeatus

Abstract: Ontogenetic change in the visual acuity of Premnas biaculeatus larvae was determined both behaviourally and anatomically. Visual acuity improved substantially between early feeding (day 3 post-hatch) and the pre-settlement (day 10 post-hatch) larvae but, at both ages, the anatomically-measured visual acuity was greater than that determined behaviourally. It appears that estimated anatomical visual acuity values substantially over-estimate the functional visual acuity realized under normal conditions. The distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 22 publications
3
51
1
3
Order By: Relevance
“…For coral reef fishes, recent findings have shown that larvae have well-developed sensory abilities and may have the potential to locate reefs and actively search for suitable settlement sites (see recent reviews by Montgomery et al 2001, Kingsford et al 2002, Leis & McCormick 2002. On small scales, both visual (Job & Bellwood 1996 and chemosensory (Arvedlund & Nielsen 1996, Arvedlund et al 1999 cues may be used for active habitat selection by settling larvae. On a larger scale, several in situ experiments have demonstrated that late-stage larvae are capable of responding to the presence of reefs at considerable distance (Leis et al 1996, Leis & Carson-Ewart 1999.…”
Section: Amphiprion Melanopus Amphiprion Percula Pomacentrus Moluccensismentioning
confidence: 99%
“…For coral reef fishes, recent findings have shown that larvae have well-developed sensory abilities and may have the potential to locate reefs and actively search for suitable settlement sites (see recent reviews by Montgomery et al 2001, Kingsford et al 2002, Leis & McCormick 2002. On small scales, both visual (Job & Bellwood 1996 and chemosensory (Arvedlund & Nielsen 1996, Arvedlund et al 1999 cues may be used for active habitat selection by settling larvae. On a larger scale, several in situ experiments have demonstrated that late-stage larvae are capable of responding to the presence of reefs at considerable distance (Leis et al 1996, Leis & Carson-Ewart 1999.…”
Section: Amphiprion Melanopus Amphiprion Percula Pomacentrus Moluccensismentioning
confidence: 99%
“…Although larvae exhibit some degree of shrinkage (approx. 10%), this varies among ages and parameters (Job & Bellwood 1996). For consistency, all values are based on raw (non-corrected) measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature and photoperiod are similar to conditions on the Great Barrier Reef lagoon during the summer peak reproductive period. Larvae were reared using a modification of the techniques described in Job et al (1997). Larvae were fed with freshly collected size-sorted wild-caught zooplankton throughout the larval stage to ensure that there was no conditioning to abnormal prey items (e.g., rotifers).…”
Section: Methodsmentioning
confidence: 99%
“…Shrinkage was estimated to be approximately 10% except for the lens diameter, where shrinkage was assumed to be negligible (cf. Job and Bellwood 1996). Measurements were adjusted for shrinkage prior to the analyses.…”
Section: Methodsmentioning
confidence: 99%